Barriers to Industrial Energy Efficiency. Issue 3 (19th August 2014) - Lunt, Peter; Ball, Peter; Levers, Andrew; Dey, PrasantaKumar; Dey, PrasantaKumar
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose Energy consumption is a significant contributor to the economic and environmental components of industrial sustainability and there is a significant body of knowledge emerging on the technical steps necessary to reduce that consumption. Achieving technical success requires organisational alignment, without which barriers to energy efficiency can be experienced. The purpose of this research is to capture organisational barriers that can inhibit energy reduction in manufacturing. Design/methodology/approach The research uses a theory building – theory testing cycle to propose and then verify existence of barriers to industrial energy efficiency. Literature review is used to build potential organisational barriers that can arise. The existence of barriers is then verified in industrial energy reduction projects using interview, observation and document analysis. Findings are validated by company staff. Findings From the literature barriers that can be related to energy reduction projects are uncovered. The generic and energy reduction specific barriers are confirmed and two new barriers are identified. A cognitive map linking the relationships between all the barriers is proposed. Research limitations/implications The research is built on detailed examination of a number of projects in a single company and work is needed to verify the findings in companies of different size and different industrial sector. Practical implications The list of barriers created can support industry in preparing for and undertaking energy efficiency projects. The cognitive map proposed will help industry and academia understand why removing current prominent barriers can lead to new barriers surfacing. Originality/value The novelty of this research is in both the creation of a list of organisational barriers for energy efficiency as well as identifying the relationships between them. The work brings generic change management barriers to enhance the specific energy reduction barriers together into a broader collation of barriers as well as uncovering new barriers. The work proposes a cognitive map of industrial energy efficiency barriers to demonstrate their interrelationships.